Digital transformation in finance: Examining economic development strategies through the lens of crowdfunding - Sallami, Mourad; Inoubli, Chiheb Eddine (International Journal of Emerging Trends in Social Sciences, 2024)
This research investigates the challenges obstructing the integration of crowdfunding into the national economy as a tool for economic development. In 2018, the Central Bank of Tunisia explored the use of crowdfunding for innovative startups, initiating fundraising efforts after a meeting with the governor and members of the Tunisian diaspora. Drawing from 10 semi-structured interviews, each averaging 1 hour and 10 minutes, as well as an analysis of crowdfunding platforms such as Cofundy and Afrikwity, and a review of blogs and social networks, the study identifies both internal and external barriers. Internal obstacles include a lack of trust and poor coordination among participants, while external challenges involve the absence of a legal framework, limited state support, and insufficient market information. The findings suggest that while these barriers pose significant difficulties, they are not insurmountable, highlighting opportunities for improvement in policy and market structures to foster the growth of crowdfunding in Tunisia.